2008
DOI: 10.1038/ng.72
|View full text |Cite
|
Sign up to set email alerts
|

The same sequence variant on 9p21 associates with myocardial infarction, abdominal aortic aneurysm and intracranial aneurysm

Abstract: Recently, two common sequence variants on 9p21, tagged by rs10757278-G and rs10811661-T, were reported to be associated with coronary artery disease (CAD) and type 2 diabetes (T2D), respectively. We proceeded to further investigate the contributions of these variants to arterial diseases and T2D. Here we report that rs10757278-G is associated with, in addition to CAD, abdominal aortic aneurysm (AAA; odds ratio (OR) = 1.31, P = 1.2 x 10(-12)) and intracranial aneurysm (OR = 1.29, P = 2.5 x 10(-6)), but not with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
561
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 659 publications
(596 citation statements)
references
References 29 publications
29
561
1
5
Order By: Relevance
“…Similarly, the association of rs10811661-T allele with T2D does not apply to CAD and other arterial diseases that they have investigated. 42 Although this study confirmed the specificity of the SNP associations to CAD and T2D respectively, it is still unclear whether the two risk alleles residing in the same locus will eventually affect the same gene or functional element leading to a defect or alteration of a biological pathway that is responsible for the diseases. Therefore, the pleiotropic effect of 9p21 locus warrants further investigation.…”
Section: Gwas After Hapmap-the Progress Over the Past 5 Years The Firsupporting
confidence: 62%
See 1 more Smart Citation
“…Similarly, the association of rs10811661-T allele with T2D does not apply to CAD and other arterial diseases that they have investigated. 42 Although this study confirmed the specificity of the SNP associations to CAD and T2D respectively, it is still unclear whether the two risk alleles residing in the same locus will eventually affect the same gene or functional element leading to a defect or alteration of a biological pathway that is responsible for the diseases. Therefore, the pleiotropic effect of 9p21 locus warrants further investigation.…”
Section: Gwas After Hapmap-the Progress Over the Past 5 Years The Firsupporting
confidence: 62%
“…As the two SNPs are independent, it was unclear at that time whether the SNP that is associated with T2D is also associated with CAD/MI and vice versa. To further investigate this, Helgadottir et al 42 examined the association of these two SNPs with T2D, CAD and four other arterial diseases, and found that rs10757278-G allele is associated with CAD, abdominal aortic aneurysm and intracranial aneurysm, but not with T2D. Similarly, the association of rs10811661-T allele with T2D does not apply to CAD and other arterial diseases that they have investigated.…”
Section: Gwas After Hapmap-the Progress Over the Past 5 Years The Firmentioning
confidence: 99%
“…Recently, genome-wide association studies have demonstrated a locus on chromosome 9p21 for CAD susceptibility in Caucasians (3)(4)(5)(6)(7). Chromosome 9p21 was found to also be associated with other atherosclerotic diseases such as stroke and aneurysm (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…An example of the clinical application of SNPs is the recent description of an SNP associated with coronary heart disease (CHD). 14,15 Using appropriate sample sizes, these groups found that homozygous individuals for one specific allele have an B20-40% increased risk of developing CHD and that B20-25% of individuals analyzed are homozygous for this variant. This kind of data can identify subjects with a higher risk for specific diseases, helping to design better strategies for the management of the patients and contributing to decipher the molecular basis of this disease.…”
Section: Discussionmentioning
confidence: 99%